2015
DOI: 10.1371/journal.pone.0143484
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 Inhibits Lipopolysaccharide-Induced BPIFA1 Expression in Nasal Epithelial Cells

Abstract: Short palate, lung, and nasal epithelium clone 1 (SPLUNC1) protein is expressed in human nasopharyngeal and respiratory epithelium and has demonstrated antimicrobial activity. SPLUNC1 is now referred to as bactericidal/permeability-increasing fold containing family A, member 1 (BPIFA1). Reduced BPIFA1 expression is associated with bacterial colonization in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Interleukin 13 (IL-13), predominately secreted by T helper 2 (TH2) cells, has been found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…How these studies were executed and their materials and methods are shown in Table 2 [ 9 , 11 13 , 15 , 17 19 , 39 ]. Furthermore, Table 3 summarizes the working mechanisms utilized by BPIFA1 to protect humans from related pathogens, viral or bacterial, that infect the upper airway.…”
Section: Bpifa1 Expression and Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…How these studies were executed and their materials and methods are shown in Table 2 [ 9 , 11 13 , 15 , 17 19 , 39 ]. Furthermore, Table 3 summarizes the working mechanisms utilized by BPIFA1 to protect humans from related pathogens, viral or bacterial, that infect the upper airway.…”
Section: Bpifa1 Expression and Regulationmentioning
confidence: 99%
“…Patients with CRSwNP had higher secretion of interleukin-13 (IL-13), which appears to play a critical role in downregulating BPIFA1 expression. In nasal epithelial cells, IL-13 attenuates BPIFA1 expression by downregulating the lipopolysaccharide- (LPS-) induced activation of phosphorylated JNK and c-Jun [ 39 ].…”
Section: Upper Airway Infection and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to this, the gene expression of CCL-2 was not induced by gliotoxin and was even decreased by AFB 1 ; as CCL-2 is a chemoattractant chemokine for monocytes [ 35 ], we can hypothesize monocytes to be less involved in the inflammation process following exposure to both mycotoxins. The gene expression of IL-13, a cytokine known to contribute to airway allergies [ 36 , 37 ], was not induced either. One would expect an induction of TLR-4 gene expression after direct exposure to fungi as the involvement of this receptor in the immune response to Aspergillus fumigatus was evidenced previously [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%